The Relationship Between Load Lifting Positions and Low Back Pain (LBP) Complaints Based on The Ovako Work Posture Analysis System (OWAS) Among Porters at Kalimas Port Manado - V. Damanik, Jelita; E.W. Moningka, Maya; Lintong, Fransiska; F. Rumampuk, Jimmy; R. Danes, Vennetia (Rifa'Institute, 2024)
Introduction: Porters often face the risk of musculoskeletal injuries, including Low Back Pain (LBP), due to non-ergonomic working postures while lifting loads. LBP is a condition with an increasing prevalence, reaching 619 million cases in 2020 and projected to rise to 834 million by 2025. In Indonesia, the prevalence of joint disorders is recorded at 7.3%, while in North Sulawesi, the prevalence of musculoskeletal disorders reached 24.7% in 2018, with a significant increase in LBP cases in 2019. Objective: This study aims to analyze the relationship between load-lifting positions and LBP complaints using the Ovako Work Posture Analysis System (OWAS). Methods: This research is an analytical study with a cross-sectional design involving 40 porters at Kalimas Port, Manado. Data were collected through observation, the Nordic Body Map questionnaire, and work posture assessments using OWAS. Data analysis was conducted using the Spearman correlation test. Results and Discussion: Most workers exhibited non-ergonomic work postures, such as bending their backs (100%) and lifting loads heavier than 20 kg (10%). A total of 72.5% of workers reported varying intensities of LBP complaints. Statistical analysis revealed a significant relationship between load-lifting positions and LBP complaints (p<0.001) with a strong correlation (r=0.550). Conclusion: Non-ergonomic load-lifting positions are significantly associated with LBP complaints among porters at Kalimas Port, Manado. Ergonomic improvements are necessary to reduce the risk of injurie